Indicators of Changing the Residential Balance to a Commercial One in the Karrada Municipality - Neamh, Nisreen; Talib , Rafal (Al-Adab Journal, 2025)
The municipality of Karrada witnessed changes in the residential land uses, not only on its main streets, but also on the secondary ones. The way of this change initially began as a process of penetration of the commercial activities and then it gradually increased. As the population increases, it results in a redistribution of land uses to be consistent with the new approach to population requirements in terms of quantity and quality. The aim of the study was to identify the indicators and factors that led to the reduction of the population balance in the Karrada municipality by identifying the pattern of change and the reasons that helped to change it in the neighborhoods of the study area. The study showed that there was a change in most of the residential uses in the main and secondary streets, which affected the reduction of the residential use in the residential neighborhoods.